Sharing Information as Political Praxis Among Activists for Self-managed Abortion - Braine, Naomi (Radical Teacher, 2024)
Social movements are intrinsically involved in processes of knowledge development, teaching, and learning, but this has become a central form of political action among feminist activists for self-manged abortion. Activists engage with medical protocols at multiple levels, and have made the sharing of this information with people facing unwanted pregnancies into both a vital form of resistance and of the creation of feminist knowledge at the intersections of science, community, and the political. This work has been central to maintaining and expanding access to abortion throughout the world, including in the United States since the Supreme Court Dobbs decision. The sharing and learning practices of activists for self-managed abortion, and other community-based health activists, challenge rigid structures of health education and the health sciences in particular, although their ways of thinking may be useful to educators in any setting.